Rationale and design of the randomized multicentre His Optimized Pacing Evaluated for Heart Failure (HOPE-HF) trial - Keene,D; Arnold,A; Shun-Shin,MJ; Howard,JP; Sohaib,SA; Moore,P; Tanner,M; Quereshi,N; Muthumala,A; Chandresekeran,B; Foley,P; Leyva,F; et al. (ESC Heart Failure, 2018)
AIMS: In patients with heart failure and a pathologically prolonged PR interval, left ventricular (LV) filling can be improved by shortening atrioventricular delay using His-bundle pacing. His-bundle pacing delivers physiological ventricular activation and has been shown to improve acute haemodynamic function in this group of patients. In the HOPE-HF (His Optimized Pacing Evaluated for Heart Failure) trial, we are investigating whether these acute haemodynamic improvements translate into improvements in exercise capacity and heart failure symptoms. METHODS AND RESULTS: This multicentre, double-blind, randomized, crossover study aims to randomize 160 patients with PR prolongation (≥200 ms), LV impairment (EF ≤ 40%), and either narrow QRS (≤140 ms) or right bundle branch block. All patients receive a cardiac device with leads positioned in the right atrium and the His bundle. Eligible patients also receive a defibrillator lead. Those not eligible for implantable cardioverter defibrillator have a backup pacing lead positioned in an LV branch of the coronary sinus. Patients are allocated in random order to 6 months of (i) haemodynamically optimized dual chamber His-bundle pacing and (ii) backup pacing only, using the non-His ventricular lead. The primary endpoint is change in exercise capacity assessed by peak oxygen uptake. Secondary endpoints include change in ejection fraction, quality of life scores, B-type natriuretic peptide, daily patient activity levels, and safety and feasibility assessments of His-bundle pacing. CONCLUSIONS: Hope-HF aims to determine whether correcting PR prolongation in patients with heart failure and narrow QRS or right bundle branch block using haemodynamically optimized dual chamber His-bundle pacing improves exercise capacity and symptoms. We aim to complete recruitment by the end of 2018 and report in 2020.